Adaptive immunity to Lymphocytic choriomeningitis virus: new insights into antigenic determinants. (September 2007) - Botten, Jason W; Kotturi, Maya F
Lymphocytic choriomeningitis virus (LCMV) is one of the most studied infectious disease models in mice. Human infection with LCMV can result in severe disease, ranging from aseptic meningitis in immunocompetent individuals, hydrocephalus, chorioretinitis or microcephaly in fetal infection, or to a highly lethal outcome in immunosuppressed individuals. This review examines recent advances in our understanding of the adaptive immune response to LCMV and how the cell-mediated and humoral immune responses contribute to protective immunity. New insights into the antigenicity of the LCMV proteome and the complexity of the cell-mediated immune response are addressed. We also discuss state-of-the-art approaches for T-cell epitope discovery in murine and human backgrounds and their recent application to LCMV. New findings regarding CD4 + T-cell dysregulation during chronic LCMV infection, and potential avenues for the treatment of chronic viral infection through modulation of the programmed cell death-1  receptor and/or IL-10 signaling pathways, are also evaluated.